On the so called “Roma serial killings” (Academic Journal of Internal Affairs, 2017)
The author provides an overview of the investigation and the court proceedings of a series of lethal attacks against Roma people in 2008-2009 in Hungary.
Keywords: homicide; Roma; investigation